Teachers’ Experiences and Role in the Design Process of Online Degree Programmes in Higher Education - Marjo Joshi; Mauri Kantola (Seminar.net, 2022)
Background The study was conducted at a university of applied sciences in Finland. The viewpoint is of those online degree programme teachers involved in the initial steps of design and implementation of the first online degree programmes in the organisation that follows a pedagogical strategy in all its operations.